Pengembangan Media Pembelajaran Inovatif Berbasis Aplikasi Quizizz Era New Normal - Nenden Munawaroh; Acep Rahmat; Mia Maryam Sarah; Dena Sri Anugrah (Universitas Garut, 2022)
Abstract The existence of the Covid-19 pandemic requires the Indonesian government to adopt a home-study system policy at various levels of education. This policy is accompanied by instructions for implementing distance learning or online learning (online). To facilitate online learning (online) relevant media is needed, by using the Quizizz application media which has educational value, it is hoped that students can learn innovatively so that it will be easier to carry out learning in class, especially teachers must always be able to update their teaching abilities. This study uses the Research and Development (RD) study method. This study aims to develop interactive learning media based on android applications in the form of the Quizizz application. Research development of research methods used to produce certain products, and test the effectiveness of these products. Based on the research, the results that can be achieved in the Quizizz application as a learning medium are: (1) Students' attention in using cellphones in the learning process, (2) Students' understanding of understanding questions independently, (3) Activeness, both asking questions about the material as well as evaluating and taking notes. material, (4) students' accuracy in questions and time management, (5) serenity in working on questions or quizzes. Thus, it can be concluded that the Quizizz application media is very effective in being used in the learning process. Keywords: Development; innovative learning media; quiz app. Â Abstrak Keberadaan Pandemi Covid-19 mengharuskan pemerintah Indonesia mengambil kebijakan sistem belajar di rumah di berbagai tingkat pendidikan. Kebijakan ini disertai dengan intruksi penerapan pembelajaran jarak jauh atau pembelajaran online (daring). Untuk mempermudah pembelajaran online (daring) diperlukan media yang relevan, dengan menggunakan media aplikasi Quizizz yang bernilai edukasi diharapkan peserta didik dapat belajar dengan inovatif sehingga akan lebih mempermudah dalam melaksanakan pembelajaran di kelas, terutama guru harus selalu dapat memperbaharui kemampuan mengajarnya. Penelitian ini menggunakan metode studi Research and Development (RD). Penelitian ini bertujuan untuk mengembangkan media pembelajaran interaktif berbasis aplikasi android berupa aplikasi Quizizz. Penelitian pengembangan metode penelitian yang digunakan untuk menghasilkan produk tertentu, dan menguji keefektifan produk tersebut. Berdasarkan penelitian hasil yang dapat dicapai dalam aplikasi Quizizz sebagai media pembelajaran, yakni: (1) Perhatian siswa dalam menggunakan handphone dalam proses pembelajaran, (2) Pemahaman siswa memahami soal secara mandiri, (3) Keaktifan, baik bertanya mengenai materi maupun mengevaluasi dan mencatat materi, (4) Ketelitian siswa terhadap soal dan manajemen waktu, (5) Ketenangan dalam mengerjakan soal atau kuis. Dengan demikian dapat disimpulkan bahwa media aplikasi Quizizz sangat efektif digunakan dalam proses pembelajaran. Kata-kata kunci: Pengembangan; media pembelajaran inovatif; aplikasi quiziz.